The Psychology of Consumer Empowerment : A Lesson from Seneca - Piha, Samuel; Torkki, Juhana (United States, 2025)
Consumer empowerment is widely investigated in consumer research, but the literature is still scarce on its psychological aspects. This theoretical essay aims to elucidate the position of consumer psychological empowerment within the research area of consumer empowerment. Consumer empowerment is initially analysed through a twofold conceptualisation of individual and institutional levels. Then, a synthesising framework is introduced based on the Roman philosopher Seneca’s selected writings discussing the same topics that are relevant for the two contemporary conceptualisations of empowerment. The framework suggests that a power shift from external (e.g. institutions) and internal forces (e.g. unconscious drives) to individual’s consciousness is a key to holistic empowerment. Holistic empowerment is conceptualised using the terminology of Seneca’s treatise On the Shortness of Life, in which Seneca recommends receding from the voluptuous and active, ‘engrossed’ lifestyles, towards the contemplative, ‘leisured’ lifestyle. The contemplative lifestyle may be understood to fuel empowerment, as it engenders consumers to become aware of external and internal pressures they wish to be liberated from. The essay is among the first times Seneca’s ideas have been brought to the fore in consumer research, adding to the consumer research literature that draws from the classical ideas of European antiquity. The main contribution is provided to the literature on consumer empowerment by ohering a conceptual account, based on Seneca’s writings, of the dynamic role of psychological empowerment.
Proceedings of the 49th Annual Macromarketing Conference